The Colours and Shapes of the World: Testing Predictions from Synesthesia about the Development of Sensory Associations - Spector, Ferrinne (My University, 2009)
The present collection of studies examines how sensory information is interrelated, and how that changes with age and experience. The hypotheses motivating the research were based on the sensory associations of adults who experience concrete inter/intra-sensory linkage, known as synesthesia. Adult synesthesia can inform the study of perceptual development, and even of language, because it appears to represent one way in which normal developmental mechanisms can play out. Using insights gained from adults with synesthesia, we derived novel hypotheses about cross-modal and cross-dimensional links likely to be present in early childhood and to persist in muted form in non-synesthetic adults.
The research reported in Chapters 2 and 3 was an examination of the learned and naturally biased influences on the development of one type of intermodal sensory association. Specifically, it investigated whether colour-letter associations found in adults reflect learned versus naturally-biased influences between shape and colour. Results from these two studies suggest that pre-literate children (2.5-3 years old) show natural biases to associate certain shapes to certain colours, which can be manifest as colour associations to letters. Naturally-biased associations between shape and colour appear to be based, in part, on the angularity of the shape. In addition to the same naturally biased colour letter associations found in toddlers, older children (7-9 years old) and adults showed colour letter associations that appear to be based in literacy, since they were not present in preliterate toddlers. The research reported in Chapter 4 was an examination of crossmodal associations between sound and shape. Specifically, it investigated the influences of consonant and vowel sound on the mapping of words to shape in toddlers. Results from this study suggest that the vowel sound of a nonsense word can reliably predict its association to a shape with specific characteristics (rounded versus jagged). Such natural biases may help bootstrap language learning. The research reported in Chapter 5 was an examination of cross-modal associations to odour. Specifically, it investigated whether there any consistent cross-modal associations between odour and either colour or texture. Results from this study suggest that there are consistent colour and texture associations to odours, some of which do not appear to be based in experience. Across studies, pre-literate toddlers, older children, and/or adults provide evidence that stimulus characteristics reliably relate to one another cross-dimensionally and crossmodally. Further, sensory associations in adulthood appear to result from an interplay of learning and natural biases, and non-synesthetic adults and toddlers show consistent, naturally-biased sensory associations similar to those seen in synesthesia.
The work presented in this thesis reveals the value of deriving hypotheses from the phenomenon of adult synesthesia about the interplay of learning and natural biases in the formation of sensory associations.
Keywords: synesthesia, sensory, perceptual development, colours, shapes, adulthood